Flow Cytometry Select Topics - Schmid, Ingrid (IntechOpen, 2016)
Flow cytometry - Select Topics is a collection of chapters that illustrate the constantly evolving application of flow cytometry to diverse areas of research or clinical investigations. It includes chapters on the utilization of flow cytometry in the fields of human reproduction and fertility, platelet function, apoptosis, inflammation research, leukemia immunophenotyping, and transplantation.